GEOPOLITICAL ORIENTATION OF PARTIES IN BOSNIA AND HERZEGOVINA - Simović, Vlade; Zarić, Ivan (Politeia, 2023)
Some time ago an anonymous commentator on one of the portals in Bosnia and Herzegovina wrote: 'The Serbian, Croatian, and Bosniak blocks of political parties are united only by Annex 4 of the Dayton Peace Agreement. Everything else separates them.' Such a general assessment seems unacceptable to researchers at first glance. Yet, anyone with a more profound knowledge of political parties in Bosnia and Herzegovina will largely agree with this thesis. It seems that the fate of the pluralistic space of Bosnia and Herzegovina, which has supervised sovereignty (through the action of the High Representative for Bosnia and Herzegovina) and an approved Constitution (imposed through the intervention of the United States of America in Dayton), is that it is not united by social values, by the basic political agreements of its elites, and not even by shared economic gain. An impossible state is the best diagnosis of Bosnia and Herzegovina, claimed by Nenad Kecmanović, and unstable and unfinished, claimed by almost all those informed on the situation in Bosnia and Herzegovina. The main thesis of this paper is that the geopolitical orientation of political parties in Bosnia and Herzegovina, which we investigate through their programmess and political practice, is a good way to show its internal antagonisms and the reasons for the impossibility of achieving unity, a stable and functional state. The conflict in Ukraine adds to the relevance of this paper, to which political parties and actors in Bosnia and Herzegovina heve expressed their respective stances. The paper is a methodological combination of two scientific fields: political theory and international relations.
Keywords: Political parties; plural societies; geopolitics; Bosnia and Herzegovina